PROBLEMS OF PERSONNEL POLICY IN THE ACTIVITIES OF SPORTS INSTITUTIONS - Dmitry V. Snytkin (Наука Красноярья)
The article examines the main problems of sports institutions in the direction of "Implementation of personnel policy." It has been established that the largest number of unresolved issues is associated with the remuneration system for employees of institutions. An analysis of problems in the field of labor rela-tions showed that institutions lack a system of real measurable results of activi-ty efficiency, often the tools of the "effective contact path" are used "on formal grounds," thereby reducing the motivation of string players and the effective-ness of sports institutions. It has been shown that institutions often lack a methodology for assessing the number of personnel in accordance with the state assignment, which also negatively affects work performance.